Long-term Results after CT-Guided Percutaneous Ethanol Ablation for the Treatment of Hyperfunctioning Adrenal Disorders - Nathan Elie Frenk (Clinics)
OBJECTIVES: To evaluate the safety and long-term efficacy of computed tomography-guided percutaneous ethanol ablation for benign primary and secondary hyperfunctioning adrenal disorders. METHOD: We retrospectively evaluated the long-term results of nine patients treated with computed tomography-guided percutaneous ethanol ablation: eight subjects who presented with primary adrenal disorders, such as pheochromocytoma, primary macronodular adrenal hyperplasia and aldosterone-producing adenoma, and one subject with Cushing disease refractory to conventional treatment. Eleven sessions were performed for the nine patients. The patient data were reviewed for the clinical outcome and procedure-related complications over ten years. RESULTS: Patients with aldosterone-producing adenoma had clinical improvement: symptoms recurred in one case 96 months after ethanol ablation, and the other patient was still in remission 110 months later. All patients with pheochromocytoma had clinical improvement but were eventually submitted to surgery for complete remission. No significant clinical improvement was seen in patients with hypercortisolism due to primary macronodular adrenal hyperplasia or Cushing disease. Major complications were seen in five of the eleven procedures and included cardiovascular instability and myocardial infarction. Minor complications attributed to sedation were seen in two patients. CONCLUSION: Computed tomography-guided ethanol ablation does not appear to be suitable for the long-term treatment of hyperfunctioning adrenal disorders and is not without risks.